First North Pacific records of the pointy nosed blue chimaera, Hydrolagus cf. trolli (Chondrichthyes: Chimaeriformes: Chimaeridae). Issue 1 (December 2016) - Reichert, Amber; Lundsten, Lonny; Ebert, David
Abstract The occurrence ofHydrolagus cf.trolli is reported for the first time from the central and eastern North Pacific Ocean. This is a geographic range extension for this species, as it was previously only known to occur in the southern Pacific Ocean off of Australia, New Zealand, and New Caledonia.